2017
DOI: 10.1111/jzo.12499
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of cheetahs in the Maasai Mara, Kenya and the potential for intra‐ and interspecific competition

Abstract: Competition is an important ecological factor influencing the population dynamics of carnivores especially as shifts in prey selection could have negative consequences for other members of the carnivore guild. It is therefore important to determine a species' resource requirements to help understand the potential degree and consequences of competition. Cheetahs Acinonyx jubatus compete over resources with larger carnivores, such as lions Panthera leo. While cheetahs generally favour smaller prey than lions, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 50 publications
1
37
0
1
Order By: Relevance
“…The long grass after the rainy season attracts large numbers of migratory ungulates, including the white‐bearded wildebeest ( Connochaetes taurinus ) and the common zebra ( Equus quagga ) from the Serengeti in Tanzania. Throughout the year, a large abundance of cheetah prey is still available, including resident white‐bearded wildebeest, Thomson's gazelle ( Eudorcas thomsonii ), Grant's gazelle ( Nanger granti ) and impala ( Aepyceros melampus ; Broekhuis, Thuo, & Hayward, 2018). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The long grass after the rainy season attracts large numbers of migratory ungulates, including the white‐bearded wildebeest ( Connochaetes taurinus ) and the common zebra ( Equus quagga ) from the Serengeti in Tanzania. Throughout the year, a large abundance of cheetah prey is still available, including resident white‐bearded wildebeest, Thomson's gazelle ( Eudorcas thomsonii ), Grant's gazelle ( Nanger granti ) and impala ( Aepyceros melampus ; Broekhuis, Thuo, & Hayward, 2018). …”
Section: Methodsmentioning
confidence: 99%
“…This is mainly because previous habitat selection studies have been conducted in fenced wildlife areas or in areas where the human population density is low, and therefore encounters with people, other than tourists, are minimal (e.g., Bissett & Bernard, 2007; Broomhall, Mills, & Toit, 2003; Broekhuis, Cozzi, Valeix, McNutt, & Macdonald, 2013; Pettorelli, Hilborn, Broekhuis, & Durant, 2009; Welch, Bissett, Perry, & Parker, 2015). These studies have however found that certain environmental factors, such as vegetation and habitat structure, influence cheetahs’ fitness, as it can affect hunting success (Mills, Broomhall, & Du Toit, 2004), cub survival (Broekhuis, 2018) and coexistence with other predators (Broekhuis et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In the Maasai Mara, 12% of cheetah kills are stolen (Broekhuis, Thuo, & Hayward, 2018) which could have an indirect effect on survival if the necessary energy requirements are not reached (Frid & Dill, 2002). This has been observed in other carnivores, such as leopards (P. pardus) , where females that suffered from a high rate of kleptoparasitism had lower reproductive success (Balme, Miller, Pitman, & Hunter, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the Maasai Mara, burning has been shown to increase both herbivore and carnivore abundance in areas postburn. However, burning can accelerate habitat conversion and increase habitat homogeneity, while attracting small ungulates (Anderson et al., 2016), the preferred prey species of female cheetahs with cubs (Broekhuis et al., 2018). Burning could therefore create an “ecological trap” by attracting female cheetahs to open areas where prey abundance is high, but cub recruitment is low (Schlaepfer, Runge, & Sherman, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation